Achieving naphthalimide-based aggregation-enhanced emission via the fluorophore-linker-aromatic strategy. (March 2020) - Wang, Yanni; Li, Guangyue; Zhang, Jiangwei; Jia, Yan; Pandey, Pramod; Yang, Songqiu
Abstract: The fluorophore-linker-aromatic structure has great promise to improve dyes' performance by regulating the embedded blocks. Inspired by its versatility, here we propose that aggregation-caused quenching can be converted to aggregation-enhanced emission (AEE) via the structure. To verify this speculation, we designed a novel dye with a naphthalimide-hexyl-quinazoline construction. The novel dye showed strengthened emission in aggregates, which is superior to traditional naphthalimide derivatives. The theoretical calculation and femtosecond transient spectra implied that the photoexcitation-induced geometry alteration could be restricted in the aggregated NIQZ, thus producing brighter fluorescence. On the basis of this mechanism, NIQZ was successfully applied to viscous lipid droplets visualization. This is the first work in which the fluorophore-linker-aromatic structure is utilized to fabricate AEE dye. Graphical abstract: Image 1 Highlights: The first work that fluorophore-linker-aromatic structure is proposed to fabricate aggregation-enhanced emission (AEE) dye. Conventional naphthalimide derivatives bear aggregation-caused quenching, but NIQZ exhibits a remarkable AEE feature. NIQZ has higher selectivity and photostability than the commercially available Nilered for long-term lipid droplet imaging. The emission mechanism of NIQZ is significant to spread the strategy to a general approach to construct AEE systems.